A STUDY ON CONSUMER BUYING BEHAVIOUR TOWARDS AMUL PRODUCTS (WITH SPECIAL REFERENCE TO THOOTHUKUDI CITY) - Thangaraja, A.; C. Muthuraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article looks at how customers purchase Amul products, focussing on thoothukudi City specifically. To acquire data, a handy sampling procedure tool was used. This study used a sample size of 120 clients. Data is gathered via questionnaires. Positive purchasing behaviour indicates that consumers have high purchasing behaviour. To boost the company's sales even more, the product's promotional tactics can be enhanced. Consequently, the research suggests that the product has a good reach in Thoothukudi city due to the positive purchase behaviour of the consumers.